Understanding cannabis use in Singapore: profile of users and drug progression - Doris Xin Yi Chia; Charis Wei Ling Ng; Pezhummoottil Vasudevan Nair Asharani; Sabina Au Yong; Jun Wen Tan; Noor Azizah Bte Zainuldin; Samuel Kee Guan Chua; Lambert Tchern Kuang Low; Christopher Cheng Soon Cheok; Gomathinayagam Kandasami (Singapore Medical Journal)
Introduction: Cannabis has consistently been the third most commonly abused drug among drug arrestees in Singapore over the past few years. Accordingly, this study aimed to understand the profile of cannabis users in Singapore and explore the effects of cannabis use on drug progression. Methods: A total of 450 participants who had used cannabis at least once in their lifetime were recruited from the National Addictions Management Service, prisons, the Community Rehabilitation Centre and halfway houses from August 2017 to May 2018. A face-to-face questionnaire was administered and descriptive analyses were conducted. Results: The mean participant age was 40.9 ± 14.51 years, and 93.1% of them were male. The participants generally initiated cannabis use during adolescence, at a mean onset age of 16.5 ± 4.46 years. Most (89.6%) were introduced to cannabis by peers. Approximately half of them (46.9%) had used cannabis before other illicit drugs and 42.1% of them had used heroin as the succeeding drug. Conclusion: In Singapore, cannabis use is often initiated during adolescence, largely under peer influence. Cannabis users may progress to other illicit drugs, particularly heroin, later in life.